Social activism in Southeast Asia - Ford, Michele (New York : Routledge, 2013)
"Brings together cutting-edge accounts of social movements concerned with civil and political rights, globalization, peace, the environment, migrant and factory labour, the rights of middle- and working-class women, and sexual identity in an overarching framework of analysis that forefronts the importance of human rights and the state as a focus for social activism in a region characterized by a history of authoritarian developmentalism and weak civil society"--Provided by publisher.
Social activism in Southeast Asia : an introduction / Michele Ford -- Southeast Asian activism and the limits to independent political space / Garry Rodan -- Separatism in Aceh : from social rebellion to political movement / Edward Aspinall -- Philippine contention in the democratic "transitions" / Vince Boudreau -- Values and the institutionalization of Indonesia's organic agriculture movement / Nicola Edwards -- Burmese social movements in exile : labour, migration and democracy / Dennis Arnold -- Labour activism in Thailand / Andrew Brown and Sakdina Chatrakul Na Ayudhya -- The anti-globalization movement in the Philippines / Dominique Caouette and Teresa Tadem -- Activism and aid : shaping the peace movement in Timor-Leste / Thushara Dibley -- International agendas and sex worker rights in Cambodia / Larissa Sandy -- Sexuality rights activism in Malaysia : the case of Seksualiti Merdeka / Julian C.H. Lee -- The Christian right and the Singaporean feminist movement / Lenore Lyons.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Social movements -- Southeast Asia; Social action -- Southeast Asia; Southeast Asia -- Social conditions -- 21st century; Electronic books